2007
DOI: 10.1063/1.2694378
|View full text |Cite
|
Sign up to set email alerts
|

Rotational hysteresis of the exchange anisotropy direction in Co∕FeMn thin films

Abstract: We have investigated the effects of rotating an applied field on the exchange anisotropy in Co/FeMn thin films. When the applied field is initially along the cooling field direction, the longitudinal hysteresis loop has a maximum coercivity and the transverse hysteresis loop is flat, indicating that the exchange field is along the cooling field direction. When the applied field angle is rotated away and then restored to the original field cooling direction, the exchange anisotropy direction has changed. The ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…4. Rotatable anisotropy field reported in previous publications [15][16][17][18][19][20][21] is usually small, which is less than a hundred Oe but in our case it can reach up to 600 Oe. Due to the contribution of this huge rotatable anisotropy field, the resultant dynamic magnetic anisotropy is large even though exchange bias field is small and as a consequence [see Eq.…”
Section: Introductioncontrasting
confidence: 48%
See 1 more Smart Citation
“…4. Rotatable anisotropy field reported in previous publications [15][16][17][18][19][20][21] is usually small, which is less than a hundred Oe but in our case it can reach up to 600 Oe. Due to the contribution of this huge rotatable anisotropy field, the resultant dynamic magnetic anisotropy is large even though exchange bias field is small and as a consequence [see Eq.…”
Section: Introductioncontrasting
confidence: 48%
“…Rotatable anisotropy found to be associated with exchange bias long time ago [15] is an angle-independent effect and manifests itself as an isotropic shift of the system energy [16]. This phenomenon is believed to result mostly from the instabilities of AF grains or domains [16][17][18] causing rotational hysteresis in high field [19], isotropic ferromagnetic resonance field shift [16], rotation of exchange field direction [20] and also having an influence on magnetization reversal [21]. It was also found that the rotatable anisotropy is most pronounced when the AF thickness is near the critical thickness for the onset of exchange bias [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…25,28,29,35,36 For some systems, rounded transitions in M ʈ and larger M Ќ values are found in the descending branch, 20,21,[25][26][27][28][34][35][36] where the field is applied parallel to the exchange-bias direction, while other systems display the opposite behavior. [21][22][23][24][25][29][30][31][32][33] Our results indicate that this discrepancy is related to the difference between a collinear and a noncollinear anisotropy case. Moreover, the nature of the anisotropy can be unambiguously deduced from the angular dependence of the hysteresis loops.…”
Section: Resultsmentioning
confidence: 74%
“…Asymmetries in the magnetization reversal have been observed for many FM/AFM systems with both in-plane [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and perpendicular 35,36 anisotropy for the FM layer. In general, rotation processes are more relevant in one branch of the hysteresis loop, in which a larger density of domains during irreversible domain nucleation processes is also observed.…”
Section: Resultsmentioning
confidence: 98%
“…[3][4][5][6][7][8][9][10] Moreover, the asymmetry depends on the angle between the external field and the exchange bias direction. 3,4,11 A method to probe the magnetization reversal processes is to use experimental techniques that provide information on the vectorial character of the magnetization such as Kerr magnetometry, 4 Kerr observation, 6 or polarized neutron reflectivity. 9 The existence of transverse magnetization is interpreted as coherent magnetization rotation, 4,11 while the flatness of the transverse magnetization indicates that there are no net rotation of the ferromagnetic ͑F͒ moments in the direction perpendicular to the applied field during the magnetization reversal ͑i.e., incoherent rotation 12 or domain wall propagation͒.…”
mentioning
confidence: 99%